Swoboda zrzeszeń w kontekście społeczeństwa obywatelskiego (aspekty filozoficzne i teoretycznoprawne) - Breczko, Anetta; Miruć, Alina (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2017)
The present paper aims at underlying the main philosophical and law-theory aspects dealing with freedom of association in the context of civil society. The concept of civil society may be subject to diverse interpretations. Regardless all the differences in its understanding, the notion implies some universal principles and values, such as freedom and responsibility, sovereignty and partnership, national identity, subsidiarity and participation, solidarity and social justice. According to classical interpretations of civil society, its most important feature is the process of self-organizing, by creating associations and institutions independent of State authority. Civil society is usually placed between public and private sphere, which fills the remaining space in social relations. Volunteer civic engagement contributes to multiply the common welfare, bringing benefits not only for individuals, but also for the government, by providing, for example, social care and education. The latter is possible only under a fully democratic and lawful state, in which pluralism and freedom of association are guaranteed.
Keywords: authority; civil society; freedom; democratic state of law; freedom of association; third sector; right of association